Coping strategies and exam anxiety in college students - Casari, Leandro Martín (2014)
This paper analyzed the coping strategies and exam anxiety in 140 Psychology majors at the University of the Aconcagua, in the state of Mendoza. It also evaluated the differences and the relationship between these two variables according to gender, completed courses and academic year. Results showed that the coping strategies included the Search for Alternative Bonuses and Emotional Discharge; students also reported a low level of anxiety. Significant associations were found between these two variables, as well in relation to gender and theacademic year. No significant results were found in the relationship with completed courses.